Impact of Front-line Demonstrations on Integrated Crop Management in Watermelon (Citrullus lanatus L.) - Madhushekar, B. Raja; Narendar, G.; Goverdhan, M.; Kumar, K. Avil (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was conducted in ten villages under DAATTC, five each in Nalgonda and Bhuvanagiri districts, Telangana, India operational areas during 2018–19 to 2020–21. Total 30 demonstrations were laid out on farmers’ fields in the districts (15 in each district). The main objective of front-line demonstrations (FLDs) was to demonstrate the integrated crop management practices in Water melon for getting higher yields over farmers’ practice. The study was undertaken to do a formative and summative (outcome and impact) evaluation of the frontline demonstrations on integrated crop management in watermelon. Data was collected with the help of structured interview schedule. The result of present study revealed that average highest yield recorded was 42.95 t ha-1 in demonstration plot over control (30.57 t ha-1) and 40.31% average yield increase was recorded over control plot. The extension gap ranged from 10.4 t ha-1 to 16.65 t ha-1 and technology gap ranged between 13.15 t ha-1 to 27.5 t ha-1 respectively with the technology index of 33.92% during the demonstration years. Besides this, the demonstrated plots gave higher gross returns, net return with higher benefit cost ratio when compared to farmers’ practice. In present study efforts were also made to study the impact of FLD on horizontal spread which has increased by 115%. The study also revealed that there was significant and positive relationship between farming experience, labour source, farm size and yield whereas age, education and family size didn’t have any significant effect on the yield.